KEWARGAAN DAN POLITIK PENGAKUAN: PEMENUHAN HAK DASAR KORBAN LUMPUR LAPINDO - Sekar Ayu (2023)
The Lapindo Mud Disaster forced the victims to relocate, thus changing their administrative identity. Therefore, the government plans to merge sub-districts and villages as a solution to restore order to the administration of victims after relocation. This study describes the Sidoarjo District Government's plan to combine sub-districts and villages from the perspective of the victims of the Lapindo Mudflow using the concepts of citizenship and the politics of recognition. The method used in this research is the descriptive-qualitative method through primary and secondary data collection. The author collected primary data through interviews with four research subjects, consisting of two victims, one Siring Village official, and one Director of Walhi East Java. The author then analyzes this research using narrative analysis techniques. The results of this study indicate that the victims reject the plan to merge sub districts and villages and demand the fulfillment of their citizenship rights in the form of social rights, political rights, and civil rights, as well as the political recognition of their real identities.